Results and implications of objective fatigue and performance measurements in five European Air Traffic Service Providers - Marsman, L.A.; Bos, T.J.J.; Verhoeven, R.P.M.; Cabon, P.; Vrancken, P.; Drongelen, A. van (Elsevier, 2025)
Air Traffic Controllers (ATCOs) face numerous fatigue-related challenges due to irregular working hours and demanding workload. The objective of this study was to determine how fatigue can be objectively monitored in the ops room and how they relate to subjective ratings. To do so, objective fatigue (eye tracking) and performance (PVT) data was gathered in five ATSPs (N=20). Alongside the objective measurements, fatigue (SP), sleepiness (KSS), and workload (ISA, RSME) questionnaires were administered. Measurements took place during ten so-called fatigue hotspot shifts, which were determined using both biomathematical and expert analyses. The results show that mean fatigue and sleepiness experienced during the shifts was moderate and below critical levels for a majority of the time. A clear increase in fatigue could be seen throughout shifts, as shown by the difference between mean subjective fatigue levels before and after duties, and corresponding PVT metrics. Significant correlations were found between subjective fatigue and sleepiness ratings on the one hand, and eye tracking metrics reflecting the percentage of time the eyes were closed for more than 70 or 80 percent (PERCLOS70 and 80) on the other hand. No significant correlations were found between subjective fatigue and sleepiness ratings and any of the PVT metrics. Furthermore, no significant correlations were found between the eye tracking metrics and the subjective workload ratings. The outcomes of this study underline that different types of fatigue-related outcome measures (subjective, objective, performance based) reflect different concepts and should be seen as complementary to one another when measuring fatigue in ATCOs. As such, relying on self-reported ratings alone may not offer a comprehensive understanding of individual fatigue levels and associated performance capabilities. The feasibility of using current objective measurement techniques by ATSPs themselves is however quite low, given the time, labour and operational constraints involved. Future research could thus target technological developments such as wireless EEG, fNIRS, speech analysis, and webcam-based eye tracking to assess fatigue in a more accessible and unobtrusive way.
Peer-review under responsibility of the scientific committee of the European Association for Aviation Psychology Conference EAAP 35